Temperature variability in southern Europe over the past 16 500 years constrained by speleothem fluid inclusion water isotopes - J. L. Bernal-Wormull; A. Moreno; Y. Dublyansky; C. Spötl; R. Giménez; C. Pérez-Mejías; M. Bartolomé; M. Arriolabengoa; E. Iriarte; I. Cacho; R. L. Edwards; H. Cheng; et al. (Climate of the Past)
In the Northern Hemisphere, the last 16.5 kyr was characterized by abrupt temperature transitions during stadials, interstadials, and the onset of the Holocene. These changes are closely linked to large-scale variations in the extent of continental ice sheets, greenhouse gas concentrations, and ocean circulation. Speleothems and their fluid inclusions serve as valuable proxies, offering high-resolution chronologies and quantitative records of past temperature changes for understanding global and regional climate mechanisms in the past. Here, we present a record based on five speleothems from two caves on the northeastern Iberian Peninsula (Ostolo and Mendukilo caves). Using hydrogen isotopic composition of fluid inclusions and rainfall samples, we developed a δ2H/T<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="35pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="3ee35efc892c2a4601da071964bde45e"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="cp-21-1235-2025-ie00001.svg" width="35pt" height="15pt" src="cp-21-1235-2025-ie00001.png"/></svg:svg> transfer function in order to reconstruct regional temperatures over the past 16.5 kyr (Ostolo–Mendukilo Fluid Inclusion Temperature record, OM-FIT). Our novel findings reveal abrupt temperature changes in SW Europe during the last deglaciation and Early Holocene, at millennial and centennial scales, anchored by a precise chronology. At the onset of Greenland Interstadial 1, the OM-FIT record shows an increase of 6.7 ± 2.8 °C relative to the cold conditions of the preceding Greenland Stadial 2.1a. During the early phase of Greenland Stadial 1, OM-FIT records a temperature decline of 6.1 ± 2.8 °C. The end of this cold phase and the onset of the Holocene are marked by a rapid warming of about 5 °C, reaching a maximum at 11.66 ± 0.03 kyr BP. The OM-FIT record also exhibits abrupt events during the Holocene (e.g., the 8.2 kyr event), which are also reflected in the δ18O values of the calcite. These abrupt temperature changes during the last deglaciation and the Holocene correspond to variations seen in paleotemperature records across Europe and in Greenland ice cores. This clearly and quantitatively illustrates the influence of changes in the Atlantic Meridional Overturning Circulation, driven by subarctic freshening, on the climate of southern Europe.